On Building an Instrument to Assess the Organizational Climate of Agile Software Development Teams - Dutra, Eliezer; Diirr, Bruna; Santos, Gleison (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2023: Anais do XXII Simpósio Brasileiro de Qualidade de Software, 2023)
Background: Measuring the organizational climate of agile teams is a challenge for practitioners, mainly due to the scarcity of specific instruments for the agile context. Not assessing specific human factors that contribute to the formation of agile the teams’ climate inhibits the capacity for an assertive diagnosis, entailing difficulties for analyzing possible causes of problems and the execution of corrective actions within climate management. Objective: We aim to investigate how to support the organizational climate assessment of agile teams considering the influence of human factors. Method: Design Science Research (DSR) was used to develop TACT (“insTrument to Assess the organizational ClimaTe of agile teams”). We performed a Qualitative Study, a Tertiary Study, and a Systematic Literature Review to establish, refine, and delimit the DSR project elements. Three case studies were performed to evaluate and identify improvement points in TACT. Finally, a survey was conducted to validate TACT’s factor structure. Result: We identified 38 human factors that influence the Teams’ Climate. The psychometric properties of 19 climate measures representing more than 80 dimensions involving a variety of constructs were investigated. TACT was grounded in the most critical human factors that influence agile development. In the three case studies, we considered evidence from multiple sources, e.g., interviews, open-ended questions, reliability and validity indexes, and an evaluation using TAM (Technology Acceptance Model), to identify improvements and investigate the capability and quality of TACT to assess the teams’ climate. Our latest investigation, the Validation Study, showed evidence of TACT theoretical structure plausibility. Conclusion: The results revealed that the TACT has good psychometric properties and provides professionals and researchers with a robust means to assess the ten critical dimensions for agility.